Nonprofit law for colleges and universities essential questions and answers for officers, directors, and advisors - Hopkins, Bruce R. (Wiley nonprofit authority series, 2011)
"A hands-on guide to the most pertinent and critical legal issues facing those who lead and manage tax-exempt colleges and universities Nonprofit Law for Colleges and Universities is a practical, accessible guide to nonprofit law as it is specifically applicable to exempt colleges and universities, and their related entities, such as fundraising foundations, endowment funds, supporting organizations, for-profit subsidiaries, and limited liability companies. Topics discussed will include governance, endowment funds management, the annual reporting requirements, and the unrelated business rules Written by the country's leading authorities on tax-exempt organizations Features essential, practical legal information in easy-to-understand English Presented in question-and-answer format, divided according to major topic areas that are of interest to those who lead and manage tax-exempt colleges and universities Designed for the management and leadership of colleges and universities, as well as others working in the higher education field, such as lawyers, accountants, and fundraising/development personnel, Nonprofit Law for Colleges and Universities allows readers to easily search for and find answers to questions, putting all the information they need right at their fingertips"--